Feasibility Analysis Model of Transformation from Real Economy to Virtual Economy Based on Association Rule Algorithm - Jing Gao (Hindawi Limited, 2021)
The transformation of the real economy to the virtual economy is one of the necessary ways for social and economic development. By analyzing the definition of real economy and virtual economy, the relationship between them, and the relationship between finance and virtual economy, a feasibility analysis model for the transition from real economy to virtual economy is designed based on association rule algorithm, and provide feasibility analysis for “from entity to virtual.” At the same time, based on the scale measurement theory of virtual economic cycle, this paper establishes the rule-constrained Apriori algorithm model. Then, the input-output structure decomposition method is used to analyze the feasibility of the transformation from the real economy to the virtual economy. Through the analysis, we know that the multiplier value in the real economy is higher than that in the virtual economy, which promotes the substantial growth of its own output. The total amount of virtual economy is growing rapidly, but economic transformation is incomplete. The expansion of the real economy has increased the total output value of virtual laser machines. Therefore, the feasibility of transforming from a real economy to a virtual economy has a good relationship.